2017
DOI: 10.4254/wjh.v9.i10.519
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy before and neurological complications after liver transplantation have no impact on the employment status 1 year after transplantation

Abstract: AIMTo investigate the impact of hepatic encephalopathy before orthotopic liver transplantation (OLT) and neurological complications after OLT on employment after OLT.METHODSOne hundred and fourteen patients with chronic liver disease aged 18-60 years underwent neurological examination to identify neurological complications, neuropsychological tests comprising the PSE-Syndrome-Test yielding the psychometric hepatic encephalopathy score, the critical flicker frequency and the Repeatable Battery for the Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The patients included into this analysis took part in a long-term follow up study of patients after liver transplantation performed at Hannover Medical School, Hannover, Germany. For a detailed description of the patient cohort see [14].…”
Section: Methodsmentioning
confidence: 99%
“…The patients included into this analysis took part in a long-term follow up study of patients after liver transplantation performed at Hannover Medical School, Hannover, Germany. For a detailed description of the patient cohort see [14].…”
Section: Methodsmentioning
confidence: 99%
“…For neuropsychological testing, treatment with CNIs presents a bias that may not be easily overcome in these studies. Nevertheless, a recent report found that although the dosage of CNIs affected neuropsychological testing, there was no impact on brain atrophy as assessed by brain MRI …”
Section: Neurocognitive Complications After Ltmentioning
confidence: 97%
“…Although two‐thirds of patients with cirrhosis exhibit neurocognitive abnormalities prior to LT, 20% still show impairment long after the procedure, despite normal liver function tests and the absence of HE before LT. Although CNIs have been implicated as possible contributors, they cannot account for all the reported abnormalities . Because the gross neurological examination is frequently normal, neurocognitive‐associated complications are usually considered if quality of life is affected or after concerns are raised by the caregivers.…”
Section: Neurocognitive Complications After Ltmentioning
confidence: 99%
“…(73,79) Second, based on the underlying etiology for the cognitive dysfunction, patients could take longer to demonstrate selfefficacy, (80) although this does not always translate to loss of employment and income. (81) Last, those with serious neurological complications, including encephalopathies, seizures, and central pontine myelinolysis, have a higher morbidity than those without them. (71,82) To conclude, the cognitive deficits associated with CHE and OHE are partly reversed after LT.…”
Section: Post-liver Transplantation Cognitive Dysfunctionmentioning
confidence: 99%